Details of the Vedibandha (basal mouldings) - Temples of India Project Team (Jio Institute, 2024)
The details of the vedibandha (basal mouldings) of the southern garbhagriha (sanctum sanctorum) of the Mahakal Temple show that it consists of khura (hoof), kapotapalika (cyma recta), kumbha (pot), and kalasha (pitcher) mouldings. The stambhas (buttresses) filling the space between bhadras (central offset) of the jangha (wall) is also ornamented.